DESCRIPTION OF SELF EFFICACY POST GROUP ACTIVITY THERAPY (TAK) IN PEOPLE WITH MENTAL DISORDERS IN THE GILINGAN PRIMARY HEALTHCARE - Norman Wijaya Gati; Nazaruddin Latif (Gaster, 2022)
Introduction :People with Mental Disorders (ODGJ) tends to increase, this is a concern to provide services. The implementation for ODGJ depends on several factors, one of which is self-efficacy. OGDJ who have high self-efficacy are expected to be able to make the right decisions according to the patient's condition, such as ability to take regular medication. By taking medication regularly, the signs and symptoms of ODGJ are under control. The purpose of this study was to determine the self-efficacy of ODGJ after group activity therapy. The method used is descriptive using cross sectional method. A total of 10 respondents were measured for their self-efficacy abilities and then performed a univariate analysis to see the self-efficacy scores. The results of this study showed that 60% of respondents had high self-efficacy. The conclusion is that most respondents have high self-efficacy after group activity therapy is carried out.Â